Frequency of Neurological Diseases After COVID-19, Influenza A/B and Bacterial Pneumonia - Zarifkar, Pardis; Peinkhofer, Costanza; Benros, Michael E.; Kondziella, Daniel (Frontiers in Neurology, 2022)
Introduction. COVID-19 might affect the incidence of specific neurological diseases, but it is unknown if this differs from the risk following other infections. Here, we characterized the frequency of neurodegenerative, cerebrovascular, and immune-mediated neurological diseases after COVID-19 compared to individuals without COVID-19 and those with other respiratory tract infections. Methods. This population-based cohort study utilized electronic health records covering ~50% of Denmark’s population (n=2,972,192). Between 02/2020 and 11/2021, we included individuals tested for COVID-19 or diagnosed with community-acquired bacterial pneumonia in hospital-based facilities. Additionally, we included individuals tested for influenza in the corresponding pre-pandemic period between 02/ 2018 and 11/2019. We stratified cohorts for in- and outpatient status, age, sex, and comorbidities. Results. 919,731 individuals were tested for COVID-19, of whom 43,375 tested positive (35,362 outpatients, 8,013 inpatients). Compared to COVID-negative outpatients, COVID-19 positive outpatients had an increased RR of Alzheimer’s disease (RR=3.5; 95%CI: 2.2-5.5) and Parkinson’s disease (RR=2.6; 95%CI: 1.7-4.0), ischemic stroke (RR=2.7; 95%CI: 2.3-3.2) and intracerebral hemorrhage (RR=4.8; 95%CI: 1.8-12.9). The RR for ischemic stroke was increased in COVID-19 inpatients compared to influenza inpatients (RR=1.7; 95%CI: 1.2-2.4) and bacterial pneumonia inpatients (only in those ≥80 years) (R=2.7; 95%CI: 1.2-6.2). Frequencies of multiple sclerosis, myasthenia gravis, Guillain-Barré syndrome and narcolepsy did not differ after COVID-19, influenza and bacterial pneumonia. Conclusion. The risk of neurodegenerative and cerebrovascular, but not neuroimmune, disorders was increased among COVID-19 positive outpatients compared to COVID-negative outpatients. However, except for ischemic stroke, most neurological disorders were not more frequent after COVID-19 than after other respiratory infections.